1987
DOI: 10.1128/aac.31.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Candida morphology on amphotericin B susceptibility

Abstract: We showed that brief exposures to amphotericin B (AmB) inhibited the induction of new Candida germ tubes and the lengthening of partially induced germ tubes. Blastoconidia with germ tpbes were more susceptible to AmB killing, and this varied directly with the induction period and the AmB exposure period. AmB did not preferentially affect germ tube adherence to fibrin matrices.We recently showed that sublethal concentrations of amphotericin B (AmB) inhibited germ tube formation in Candida albicans cultures (7).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…The intracellular efficacies of the antifungal agents were determined in terms of inhibition of germ tube formation as well as effective killing of C. albicans intracellularly. With AmB, inhibition of the development of germ tubes was found at concentrations lower than those required for killing of intracellular C. albicans, which has also been reported by others (25,26,38). After an increase in the ratio of infection, slightly increased AmB concentrations were required to obtain both effects.…”
Section: Discussionsupporting
confidence: 59%
“…The intracellular efficacies of the antifungal agents were determined in terms of inhibition of germ tube formation as well as effective killing of C. albicans intracellularly. With AmB, inhibition of the development of germ tubes was found at concentrations lower than those required for killing of intracellular C. albicans, which has also been reported by others (25,26,38). After an increase in the ratio of infection, slightly increased AmB concentrations were required to obtain both effects.…”
Section: Discussionsupporting
confidence: 59%
“…Although our results with respect to the inhibition of germ tube formation and elongation were consistent with observations reported by others for AmB (Nugent and Couchot 1986;Nugent et al 1987;Schaude et al 1987) and the imidazoles (Borgers et al 1979(Borgers et al , 1983Davies and Marriott 1981;Odds et al 1985;Shibl 1985;Sobel and Obedeanu 1983), correlating these events to subsequent reductions in the in vitro interaction of C. albicans with mammalian cells have not been previously reported. The results presented here also seem to indicate that while germ tube formation may be a prerequisite for fibroblast infection, modification of germinated cells by AmB may be sufficient to prevent yeast-fibroblast interactions.…”
Section: Effect Of Amb On Germ Tube Elongationsupporting
confidence: 90%
“…Our results also suggested that infection correlated with blastoconidial germination. Since recent reports have demonstrated that sublethal concentrations of amphotericin B (AmB) inhibited blastoconidial germination (Nugent and Couchot 1986;Nugent et al 1987;Schaude et al 1987), we tested the effects of sublethal amounts of ArnB on the germination of our clinical isolates and on their subsequent ability to interact with fibroblastic monolayer cultures. This report describes the results of these experiments.…”
Section: Introductionmentioning
confidence: 99%
“…There are also differences in composition of the plasma membranes of yeast and filamentous forms of C. albicans (6,32). Yeast organisms with germ tubes were more susceptible to the action of amphotericin B than nongerminated yeast organisms (34). However, it could be argued that the yeast organisms in the process of producing germ tubes were those more actively growing.…”
Section: Discussionmentioning
confidence: 81%